2018
DOI: 10.3390/ijerph15081684
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Burden of Food Insecurity among Asian Americans: Results from the California Health Interview Survey

Abstract: Objective: Food insecurity remains a major public health issue in the United States, though lack of research among Asian Americans continue to underreport the issue. The purpose of this study was to evaluate the prevalence and burden of food insecurity among disaggregated Asian American populations. Methods: The California Health Interview Survey, the largest state health survey, was used to assess the prevalence of food insecurity among Asian American subgroups with primary exposure variable of interest being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Maternal time in the US was an ordinal variable with five levels: < 5 years, 5-14 years, 15-24 years, ≥ 25 years, and US-born. US nativity and increasing time in the US served as proxies for acculturation, similar to larger studies in Asian American populations [5,6,[33][34][35][36] in which acculturation questionnaires were not administered.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Maternal time in the US was an ordinal variable with five levels: < 5 years, 5-14 years, 15-24 years, ≥ 25 years, and US-born. US nativity and increasing time in the US served as proxies for acculturation, similar to larger studies in Asian American populations [5,6,[33][34][35][36] in which acculturation questionnaires were not administered.…”
Section: Methodsmentioning
confidence: 87%
“…While Asian Americans are the highest earning racial/ethnic group, they are the most economically divided, partly due to different sociopolitical histories and immigration policies that shape their experiences [44]. Furthermore, low acculturation is associated with food insecurity in most Asian American subgroups [35], and participation in the Supplemental Nutrition Assistance Program (SNAP) is low in this population [35]. Providing financial assistance to low income, less acculturated families and addressing barriers to SNAP participation may help reduce obesity in Asian American children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, due to the limitation of the HPS data, we were unable to disaggregate Asian and Hispanic categories into subgroups based on country of origin (e.g., Chinese, Vietnamese, Mexican, Cuban), which might mask substantial diversity that exists within Asian and Hispanic populations and conceal disparate food insecurity risks experienced by particular subgroups. For example, a previous study found the highest prevalence of food insecurity among Vietnamese Americans and the lowest prevalence among Japanese Americans [63]. Fifth, based on previous research and existing evidence, we provided explanations on why Asian and Hispanic households might be afraid to leave their homes to buy food.…”
Section: Study Limitations and Avenues For Further Researchmentioning
confidence: 87%
“…Further, approximately 30% of our sample had 'moderate' concerns around food insecurity. When the California Health Interview Survey (CHIS) was used to assess the prevalence of food insecurity among Asian Americans [34], the highest prevalence of food insecurity was found among Vietnamese Americans (16.42%). Factors predicting food insecurity were low acculturation and speaking a language other than English at home.…”
Section: Discussionmentioning
confidence: 99%